2020 Mark Coventry Award: Microorganism-directed oral antibiotics reduce the rate of failure due to further infection after two-stage revision hip or knee arthroplasty for chronic infection: a multicentre randomized controlled trial at a minimum of two years. (June 2020) - Yang, JaeWon; Parvizi, Javad; Hansen, Erik N.; Culvern, Chris N.; Segreti, John C.; Tan, Timothy; Hartman, Curtis W.; Sporer, Scott M.; Della Valle, Craig J.; ,
Abstract : Aims: The aim of this study was to determine if a three-month course of microorganism-directed oral antibiotics reduces the rate of failure due to further infection following two-stage revision for chronic prosthetic joint infection (PJI) of the hip and knee. Methods: A total of 185 patients undergoing a two-stage revision in seven different centres were prospectively enrolled. Of these patients, 93 were randomized to receive microorganism-directed oral antibiotics for three months following reimplantation; 88 were randomized to receive no antibiotics, and four were withdrawn before randomization. Of the 181 randomized patients, 28 were lost to follow-up, six died before two years follow-up, and five with culture negative infections were excluded. The remaining 142 patients were followed for a mean of 3.3 years (2.0 to 7.6) with failure due to a further infection as the primary endpoint. Patients who were treated with antibiotics were also assessed for their adherence to the medication regime and for side effects to antibiotics. Results: Nine of 72 patients (12.5%) who received antibiotics failed due to further infection compared with 20 of 70 patients (28.6%) who did not receive antibiotics (p = 0.012). Five patients (6.9%) in the treatment group experienced adverse effects related to the administered antibiotics severe enough to warrant discontinuation. Conclusion: This multicentre randomized controlled trial showed that a three-month course of microorganism-directed, oral antibiotics significantly reduced the rate of failure due to further infection following a two-stage revision of total hip or knee arthroplasty for chronic PJI. Cite this article: Bone Joint J 2020;102-B(6 Supple A):3–9.